High-performance SiC composite material and preparation method thereof
A one-step sintering process for SiC composites addresses performance and cost issues, enhancing mechanical and thermal stability while reducing environmental impact, resulting in high-performance and cost-effective materials.
Patent Information
- Application Number
- CN202510577077.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-07-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing SiC composite materials have shortcomings in performance, cost and environmental protection, which are difficult to meet the stability needs in high temperature environments, and the preparation process is complex, costly, and unfriendly.
A high-performance SiC composite material is prepared by using one-step sintering and low-temperature precision post-treatment, using industrial-grade α-SiC powder, petroleum coke powder, chopped carbon fiber, TiC powder, PMMA microspheres, NaCl particles and polyvinyl alcohol, combined with Al2O3-Y2O3 mixed powder as a sintering aid, and using N2/Ar/Cl2 multi-channel gas control system and hydraulic restraint ring to generate nano-scale Ti3SiC2 sheet crystals, forming connecting pores and removing residual salts.
The combination of low-cost, high-performance and green manufacturing is achieved, which significantly improves the mechanical properties, high temperature stability and surface quality of the material, reduces production costs and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material preparation, in particular to a high-performance SiC composite material and a preparation method thereof. Background Art
[0002] SiC composite materials are a type of material that uses silicon carbide (SiC) as the main component and is formed by adding other reinforcement phases or matrix phases. They can be divided into particle-reinforced SiC composite materials, fiber-reinforced SiC composite materials, and whisker-reinforced SiC composite materials. For example, in particle-reinforced SiC composite materials, silicon carbide particles are usually added to improve the strength, hardness, and wear resistance of the matrix material. They can be used to manufacture aircraft wing leading edges, engine blades, and other parts, which can reduce the weight of aircraft, improve fuel efficiency, and flight performance. They can also be used to manufacture automobile brake discs, pistons, turbochargers, and other parts to improve the performance and reliability of automobiles while reducing fuel consumption. They are also widely used in the electronics industry and energy fields.
[0003] However, the existing SiC-based composite materials have a series of problems that need to be solved in terms of performance, cost and green manufacturing. These problems limit the widespread application and further development of SiC composite materials. From the performance point of view, traditional SiC composite materials are difficult to meet the increasingly stringent application requirements in key performance indicators such as mechanical properties and thermal properties. Some SiC ceramic-based composite materials prepared by conventional sintering processes, although they have certain hardness and wear resistance, their strength and toughness will drop significantly in high temperature environments, and they cannot serve stably for a long time. In high-temperature application scenarios such as hot-end components of aircraft engines and high-temperature furnaces, this performance instability is particularly prominent, seriously affecting the reliability and service life of the equipment. In addition, when subjected to impact loads, traditional SiC composite materials are prone to brittle fracture and it is difficult to fully exert their due structural bearing function. In fields with high requirements for material impact resistance, such as protective structures of high-speed aircraft, their application is greatly restricted. At the same time, in terms of preparation cost, the current mainstream SiC composite material preparation process often involves complex processes and expensive equipment, resulting in high production costs. Secondly, the existing SiC composite material preparation technology generally has environmentally unfriendly problems. Many traditional preparation processes will generate a large amount of waste gas, wastewater and waste residue during the production process, which puts great pressure on the ecological environment. It runs counter to the current global advocacy of energy conservation, emission reduction and green development concepts, and is not conducive to the sustainable development of the materials industry. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies of the prior art, the present invention provides a high-performance SiC composite material and a preparation method thereof, which solve the problems that the existing SiC composite materials have defects in terms of cost, performance, stability, and environmental protection.
[0006] (2) Technical solution
[0007] To achieve the above object, the present invention is realized through the following technical solutions: A high-performance SiC composite material is composed of the following parts by mass: 20-35 parts of industrial-grade α-SiC powder, 10-14 parts of petroleum coke powder, 4-9 parts of short carbon fibers, 2-6 parts of TiC powder, 1-4 parts of sintering aid, 2-7 parts of PMMA microspheres, 4-11 parts of NaCl particles, and 1-3 parts of polyvinyl alcohol.
[0008] Preferably, the sintering aid adopts an Al2O3-Y2O3 mixed powder material to promote liquid-phase sintering.
[0009] A preparation method of a high-performance SiC composite material includes the following preparation steps:
[0010] S1. Immerse the short carbon fibers in a 5% nitric acid solution for 8 minutes to remove the surface colloid and enhance the bonding with the matrix.
[0011] S2. Ball-mill and mix the sintering aid in a molar ratio of 3:2 for 1.5 hours.
[0012] S3. Pour the industrial-grade α-SiC powder, TiC powder, sintering aid, and petroleum coke into a V-type mixer and mix at a low speed of 50 rpm for 2 hours to obtain mixture one.
[0013] S4. Add carbon fibers, PMMA, NaCl, and PVA solution to mixture one to obtain mixture two, then send it into a ball-mill tank, add anhydrous ethanol and zirconia balls, ball-mill for 8 h to ensure uniform dispersion, then vacuum-dry at 80 °C for 32 hours, and pass through a 100-mesh sieve to obtain a composite powder with good fluidity.
[0014] S5. Load the composite powder into a rubber mold, keep the pressure at 200 MPa for 7 minutes, and then calcine in air at 650 °C for 2 hours to remove the PVA binder.
[0015] S6. Customize a high-temperature sintering furnace with a maximum temperature of 1700 °C, equipped with an N2 / Ar / Cl2 multi-channel gas control system, and integrate a graphite mold and a hydraulic restraint ring to generate a sintered body.
[0016] S7. Immerse the sintered body in deionized water at 80 °C for 2 hours to dissolve NaCl to form connected pores, and then ultrasonically vibrate at 40 kHz for 15 minutes to remove the residual salt in the pores to obtain the SiC composite material.
[0017] Preferably, the ethanol medium in which the molar ratio balls are mixed in S2 is 300 rpm.
[0018] Preferably, in S6, nanoscale Ti3SiC2 platelets are formed by reacting TiC with SiC at a temperature above 1450 °C.
[0019] Preferably, in S6, a mass flowmeter is used to precisely control the proportion of Cl2, and the Cl content detected by surface EDS is ≤ 0.5 at%.
[0020] Preferably, in S6, a graphite mold with a removable restraint ring is integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600 °C to cause slight plastic flow on the surface of the green body and reduce the surface unevenness after sintering.
[0021] Preferably, in S6, a Cl2 / Ar gas mixture is introduced at 1200 °C to selectively etch loose SiC particles on the surface and avoid mechanical contact damage.
[0022] (III) Beneficial effects
[0023] The present invention provides a high-performance SiC composite material and a preparation method thereof. It has the following
[0024] beneficial effects:
[0025] 1. In the preparation process of the SiC composite material of the present invention, an innovative full chain of one-step sintering and low-temperature precision post-treatment is adopted, realizing the perfect combination of low cost, high performance, high stability and green manufacturing, and solving the long-term bottlenecks of traditional SiC composite materials in terms of cost, performance, processing defects, etc.
[0026] 2. The one-step sintering in the present invention can complete matrix densification, in-situ synthesis of reinforcing phases, formation of surface nitriding protective layers, in-situ repair of defects, save more than 70% of equipment investment, and shorten the production cycle by 50 - 60% in a single furnace run. These are advantages not possessed by existing preparation processes. Specific embodiments
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0028] Example 1:
[0029] An embodiment of the present invention provides a high-performance SiC composite material, which is composed of the following parts by mass: 20 parts of industrial-grade α-SiC powder, 10 parts of petroleum coke powder, 4 parts of chopped carbon fiber, 2 parts of TiC powder, 1 part of sintering aid, 2 parts of PMMA microspheres, 4 parts of NaCl particles, and 1 part of polyvinyl alcohol.
[0030] The sintering aid uses an Al2O3-Y2O3 mixed powder material to promote liquid-phase sintering.
[0031] A preparation method of a high-performance SiC composite material includes the following preparation steps:
[0032] S1. Immerse the chopped carbon fiber in a 5% nitric acid solution for 8 minutes to remove the surface colloid and enhance the bonding with the matrix.
[0033] S2. The sintering aid is ball-milled and mixed at a molar ratio of 3:2 for 1.5 hours.
[0034] S3. Pour the industrial-grade α-SiC powder, TiC powder, sintering aid, and petroleum coke into a V-type mixer and mix at a low speed of 50 rpm for 2 hours to obtain mixture one.
[0035] S4. Add carbon fiber, PMMA, NaCl, and PVA solution to mixture one to obtain mixture two, then send it into a ball mill tank, add anhydrous ethanol and zirconia balls, ball mill for 8 hours to ensure uniform dispersion, then vacuum dry at 80°C for 32 hours, and pass through a 100-mesh sieve to obtain a composite powder with good fluidity.
[0036] S5. Load the composite powder into a rubber mold, hold the pressure at 200 MPa for 7 minutes, and then calcine in air at 650°C for 2 hours to remove the PVA binder.
[0037] S6. Customize a high-temperature sintering furnace with a maximum temperature of 1700°C, equipped with an N2 / Ar / Cl2 multi-channel gas control system, and integrate a graphite mold and a hydraulic restraint ring to generate a sintered body.
[0038] S7. Immerse the sintered body in deionized water at 80°C for 2 hours to dissolve NaCl to form connected pores, and then ultrasonically vibrate at 40 kHz for 15 minutes to remove the residual salt in the pores to obtain the SiC composite material.
[0039] The ethanol medium for ball mixing at the molar ratio in S2 is 300 rpm.
[0040] In S6, nanoscale Ti3SiC2 platelets are generated by the reaction of TiC and SiC at temperatures above 1450°C.
[0041] In S6, the proportion of Cl2 is precisely controlled by a mass flow meter, and the Cl content detected by surface EDS is ≤0.5 at%.
[0042] S6 integrates a graphite mold and a detachable restraint ring in the furnace chamber, applies axial pressure during the 1600 °C heat preservation stage, causes slight plastic flow on the surface of the green body, and reduces surface unevenness after sintering.
[0043] S6 integrates a graphite mold and a detachable restraint ring in the furnace chamber, applies axial pressure during the 1600 °C heat preservation stage, causes slight plastic flow on the surface of the green body, and reduces surface unevenness after sintering.
[0044] Example two:
[0045] An embodiment of the present invention provides a high-performance SiC composite material, which is composed of the following parts by mass: 29 parts of industrial-grade α-SiC powder, 12 parts of petroleum coke powder, 8 parts of short-cut carbon fiber, 3 parts of TiC powder, 2 parts of sintering aid, 5 parts of PMMA microspheres, 7 parts of NaCl particles, and 2 parts of polyvinyl alcohol.
[0046] The sintering aid uses an Al2O3-Y2O3 mixed powder material to promote liquid-phase sintering.
[0047] A preparation method of a high-performance SiC composite material includes the following preparation methods:
[0048] S1. Immerse the short-cut carbon fiber in a 5% nitric acid solution for 8 minutes to remove the surface colloid and enhance the bonding with the matrix;
[0049] S2. The sintering aid is ball-milled and mixed at a molar ratio of 3:2 for 1.5 hours;
[0050] S3. Pour the industrial-grade α-SiC powder, TiC powder, sintering aid, and petroleum coke into a V-type mixer and mix at a low speed of 50 rpm for 2 hours to obtain mixture one;
[0051] S4. Add carbon fiber, PMMA, NaCl, and PVA solution to the inside of mixture one to obtain mixture two, then send it into a ball-milling tank, add anhydrous ethanol and zirconia balls, ball-mill for 8 h to ensure uniform dispersion, then vacuum-dry at 80 °C for 32 hours, and pass through a 100-mesh sieve to obtain a composite powder with good fluidity;
[0052] S5. Load the composite powder into a rubber mold, keep the pressure at 200 MPa for 7 minutes, then calcine in air at 650 °C for 2 hours to remove the PVA binder;
[0053] S6. Customize a high-temperature sintering furnace with a maximum temperature of 1700 °C, equipped with an N2 / Ar / Cl2 multi-channel gas control system, and integrate a graphite mold and a hydraulic restraint ring to generate a sintered body;
[0054] S7. Immerse the sintered body in deionized water at 80 °C for 2 hours to dissolve NaCl to form connected pores, then perform ultrasonic oscillation at 40 kHz for 15 minutes to remove the residual salt in the pores to obtain the SiC composite material.
[0055] The ethanol medium with a molar ratio of balls in S2 is mixed at 300 rpm.
[0056] In S6, nanoscale Ti3SiC2 platelets are formed by reacting TiC with SiC above 1450 °C.
[0057] In S6, a mass flowmeter is used to precisely control the Cl2 ratio, and the Cl content detected by surface EDS is ≤ 0.5 at%.
[0058] In S6, a graphite mold with a detachable restraint ring is integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600 °C to cause slight plastic flow on the surface of the green body, reducing the surface unevenness after sintering.
[0059] In S6, a graphite mold with a detachable restraint ring is integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600 °C to cause slight plastic flow on the surface of the green body, reducing the surface unevenness after sintering.
[0060] Example Three:
[0061] The present invention provides a high-performance SiC composite material, which consists of the following parts by mass: 35 parts of industrial-grade α-SiC powder, 14 parts of petroleum coke powder, 9 parts of short carbon fibers, 6 parts of TiC powder, 4 parts of sintering aid, 7 parts of PMMA microspheres, 11 parts of NaCl particles, and 3 parts of polyvinyl alcohol.
[0062] The sintering aid uses an Al2O3 - Y2O3 mixed powder material to promote liquid-phase sintering.
[0063] A method for preparing a high-performance SiC composite material includes the following preparation steps:
[0064] S1. Immerse the short carbon fibers in a 5% nitric acid solution for 8 minutes to remove the surface gum and enhance the bonding with the matrix.
[0065] S2. The sintering aid is ball-milled and mixed for 1.5 hours at a molar ratio of 3:2.
[0066] S3. Pour the industrial-grade α-SiC powder, TiC powder, sintering aid, and petroleum coke into a V-type mixer and mix at a low speed of 50 rpm for 2 hours to obtain Mixture One.
[0067] S4. Add carbon fibers, PMMA, NaCl, and PVA solution to the inside of Mixture One to obtain Mixture Two, then send it into a ball-milling tank, add anhydrous ethanol and zirconia balls, ball-mill for 8 h to ensure uniform dispersion, then vacuum-dry at 80 °C for 32 hours, and pass through a 100-mesh sieve to obtain a composite powder with good fluidity.
[0068] S5. Load the composite powder into a rubber mold, hold the pressure at 200 MPa for 7 minutes, and then calcine it in air at 650 °C for 2 hours to remove the PVA binder;
[0069] S6. Customize a high-temperature sintering furnace with a maximum temperature of 1700 °C, equipped with an N2 / Ar / Cl2 multi-channel gas control system, and integrate a graphite mold and a hydraulic restraint ring to generate a sintered body;
[0070] S7. Immerse the sintered body in deionized water at 80 °C for 2 hours to dissolve NaCl to form connected pores, and then ultrasonically vibrate it at 40 kHz for 15 minutes to remove the residual salts in the pores to obtain the SiC composite material.
[0071] In S2, the ethanol medium for mixing the balls at a molar ratio is 300 rpm.
[0072] In S6, nanoscale Ti3SiC2 platelets are formed by the reaction of TiC and SiC above 1450 °C.
[0073] In S6, a mass flowmeter is used to precisely control the Cl2 ratio, and the surface EDS detects that the Cl content ≤ 0.5 at%.
[0074] In S6, a graphite mold and a detachable restraint ring are integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600 °C to cause slight plastic flow on the surface of the green body and reduce the surface unevenness after sintering.
[0075] In S6, a graphite mold and a detachable restraint ring are integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600 °C to cause slight plastic flow on the surface of the green body and reduce the surface unevenness after sintering.
[0076] Comparative Example 1:
[0077] A SiC composite material prepared by the CVI method.
[0078] Experimental Example:
[0079] The three-point bending test (ASTM C1161) with a span of 30 mm and a loading rate of 0.5 mm / min is used to measure the flexural strength of the composite materials prepared in Example 1, Example 2, Example 3, and Comparative Example 1. Secondly, the high-temperature stability of the composite materials prepared in Example 1, Example 2, Example 3, and Comparative Example 1 is measured by weighing the weight gain after static air exposure at 1200 °C in a muffle furnace for 100 h. Finally, the surface roughness of the composite materials prepared in Example 1, Example 2, Example 3, and Comparative Example 1 is measured by a white light interferometer (Ra value, sampling length 0.8 mm). The specific measurement results are shown in Table 1 below:
[0080] Table 1.
[0081] Flexural strength High-temperature stability Surface roughness Example 1 680±25 <![CDATA[2.5mg / cm 2 > 0.08 Example 2 740±21 <![CDATA[3.1mg / cm 2 > 0.05 Example 3 620±17 <![CDATA[2.3mg / cm 2 > 0.1 Comparative Example 1 440±19 <![CDATA[0.7mg / cm 2 > 0.8 Improvement range 61±12% 55±6% 77±8%
[0082] In summary, through strict comparative experiments, it is verified that the one-step sintered SiC composite material prepared by the present invention comprehensively surpasses the traditional CVI material in terms of mechanical properties, high-temperature stability, and surface roughness, and the cost is reduced by more than 70%. Its core advantage lies in the process integration: sintering - strengthening - surface modification are completed in one step.
[0083] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-performance SiC composite material, characterized in that, It consists of the following parts by mass: 20 - 35 parts of industrial-grade α-SiC powder, 10 - 14 parts of petroleum coke powder, 4 - 9 parts of short carbon fibers, 2 - 6 parts of TiC powder, 1 - 4 parts of sintering aid, 2 - 7 parts of PMMA microspheres, 4 - 11 parts of NaCl particles, and 1 - 3 parts of polyvinyl alcohol.
2. A high-performance SiC composite material according to claim 1, characterized in that: The sintering aid uses an Al2O3 - Y2O3 mixed powder material to promote liquid-phase sintering.
3. A method for preparing a high-performance SiC composite material, characterized in that, It includes the following preparation method: S1. Immerse the short carbon fibers in a 5% nitric acid solution for 8 minutes to remove the surface colloid and enhance the bonding with the matrix. S2. The sintering aid is ball-milled and mixed at a molar ratio of 3:2 for 1.5 hours. S3. Pour the industrial-grade α-SiC powder, TiC powder, sintering aid, and petroleum coke into a V-type mixer and mix at a low speed of 50 rpm for 2 hours to obtain mixture one. S4. Add carbon fibers, PMMA, NaCl, and PVA solution to mixture one to obtain mixture two, then send it into a ball mill tank, add absolute ethanol and zirconia balls, and ball mill for 8 hours to ensure uniform dispersion. Subsequently, vacuum dry at 80°C for 32 hours and pass through a 100-mesh sieve to obtain a composite powder with good fluidity. S5. Load the composite powder into a rubber mold, keep the pressure at 200 MPa for 7 minutes, and then calcine in air at 650°C for 2 hours to remove the PVA binder. S6. Customize a high-temperature sintering furnace with a maximum temperature of 1700°C, equipped with an N2 / Ar / Cl2 multi-channel gas control system, and integrate a graphite mold and a hydraulic restraint ring to generate a sintered body. S7. Immerse the sintered body in deionized water at 80°C for 2 hours to dissolve NaCl to form connected pores, and then ultrasonically vibrate at 40 kHz for 15 minutes to remove the residual salts in the pores to obtain the SiC composite material.
4. A method for preparing a high-performance SiC composite material according to claim 3, characterized in that: The ethanol medium for ball mixing at a molar ratio in S2 is 300 rpm.
5. A method for preparing a high-performance SiC composite material according to claim 3, characterized in that: In S6, nanoscale Ti3SiC2 platelets are generated by the reaction of TiC and SiC at temperatures above 1450°C.
6. A method for preparing a high-performance SiC composite material according to claim 3, characterized in that: In S6, the proportion of Cl2 is precisely controlled using a mass flow meter, and the Cl content detected by surface EDS is ≤0.5 at%.
7. A method for preparing a high-performance SiC composite material according to claim 3, characterized in that: In S6, a graphite mold and a detachable restraint ring are integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600°C to cause slight plastic flow on the surface of the green body and reduce the surface unevenness after sintering.
8. The method for preparing a high-performance SiC composite material according to claim 3, wherein: In S6, a graphite mold and a detachable restraint ring are integrated in the furnace chamber, and an axial pressure is applied during the heat preservation stage at 1600°C to cause slight plastic flow on the surface of the green body and reduce the surface unevenness after sintering.
Citation Information
Cited By
Modified electrode paste as well as preparation method and application thereof
CN122393050A
A modified electrode paste, its preparation method and application
CN122393050B
